Late Intra-Uterine Fetal Demise with Fetal Hydrops: Challenges of Management Planning in Indonesia - Hermawan, Gezta Nasafir; Wibisono, Jacobus Jeno; Nainggolan, Julita D.L. (Fakultas Kedokteran Universitas Pelita Harapan, 2020)
Intra-Uterine Fetal Demise (IUFD) is defined as death of human conception at age of 20 weeks’ gestation or older or with a minimum 500-g birthweight before complete delivery from the mother and induced termination involved. In 2015, Indonesia has contributed a stillbirth rate of 13 out of 1,000 total births in which 17.1% of the cases were caused by congenital anomalies. Fetal Hydrops as a pathological condition in which there is an accumulation of fluid in fetal soft tissues and serous cavities. With the advancements of sonographic technology, identification of fetal hydrops has become uncomplicated. However, what remains a challenge is to investigate etiology and determine management. In order to plan proper management, the etiology of fetal hydrops must first be determined to predict the prognosis of fetal hydrops. In Indonesia; limited facilities and experts combined with high costs in etiology determination and management have complicated the matter. Furthermore, the strong influence of several Eastern communities’ norms and religious views have further complicated both physicians and patients in decision making. In this report, we present a case of late intra-uterine fetal demise with fetal hydrops, whom was admitted on her 35 weeks age gestation. We performed elective Caesarean Section in order to deliver the stillborn fetus, with no significant post-operative complication. Unfortunately, this condition was actually diagnosed earlier during 20th weeks of gestation, hence advised to continue the pregnancy without further evaluation and information to the mother regarding the hydrops condition.